PENGARUH KEPEMIMPINAN TRANSFORMASIONAL DAN KOMPETENSI TERHADAP KINERJA PEGAWAI DENGAN MEDIASI MOTIVASI DAN KOMITMEN ORGANISASIONAL (Studi Kasus Dinas Perindustrian dan Perdagangan Provinsi Jawa Tengah) - Noval Nixmamara, 1352020060; Abdul Rozak, Hasan (Jurnal Mahasiswa Pasca Sarjana, 2015)
This study aims to analyze and describe the effect of transformational leadership and competence on performance with the mediation of motivation and organizational commitment. To hypothesis tested by multiple linear regression with the practicing of mediation test. Transformational leadership and competence are the independent variables, while performance as the dependent variable as if motivation and organizational commitment as the mediation variables. The results of partial test showed that transformational leadership, motivation and organizational commitment have significatn effect on performance. Transformastional leadership effect on motivation and organizational commitment while competence only effect on motivation. The mediation test results showed that the effect of transformational leadership on performance could be mediated by motivation and organizational commitment while the effect of competence on performance could be given by the mediating of motivation. Keywords: Performance, Organizational Commitment, Motivation, Transformational Leadership, Competence, Mediation